2021
DOI: 10.1016/j.algal.2021.102186
|View full text |Cite
|
Sign up to set email alerts
|

The effects of illumination and trophic strategy on gene expression in Chlamydomonas reinhardtii

Abstract: Microalgae are of substantial biotechnological interest due their polyphyletic nature which grants them access to a wide array of high-value metabolites. The inherent genetic diversity of microalgae combined with their metabolic plasticity when grown using different trophic and illumination strategies necessitate the establishment of a reference knowledge base. In the present study we present a detailed characterisation of the combined effects of wavelength selection and trophic strategy on the growth kinetics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 87 publications
0
6
0
Order By: Relevance
“…Appeared biochemical trophic adjustments include complex alterations in the various pathways of central metabolism such as carbon fixation, sugar metabolism, TCA, and lipid and starch deposition [ 2 , 7 , 10 , 34 , 35 ]. These alterations are closely related to a shift in the expression of genes encoding the involved enzymes [ 4 , 6 , 36 ], which results in a redirection in metabolic fluxes [ 27 , 37 , 38 ]. The assumption is that current algae growth and metabolism would have the effect of previous trophic conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Appeared biochemical trophic adjustments include complex alterations in the various pathways of central metabolism such as carbon fixation, sugar metabolism, TCA, and lipid and starch deposition [ 2 , 7 , 10 , 34 , 35 ]. These alterations are closely related to a shift in the expression of genes encoding the involved enzymes [ 4 , 6 , 36 ], which results in a redirection in metabolic fluxes [ 27 , 37 , 38 ]. The assumption is that current algae growth and metabolism would have the effect of previous trophic conditions.…”
Section: Discussionmentioning
confidence: 99%
“…It defines the balance between synthesis and catabolism in algal cells [ 2 , 3 ]. The effect of trophic conditions on C. reinhardtii growth and metabolism has been studied at genetic, biochemical, and physiological levels through newly developed transcriptomic [ 4 , 5 , 6 ], proteomic [ 7 , 8 , 9 ], and metabolomic [ 7 , 10 , 11 ] approaches. Nevertheless, in comparison with other types of adaptation strategies [ 12 , 13 ], many processes involved in tropic adaptation are still far from known.…”
Section: Introductionmentioning
confidence: 99%
“…Varying light quality and quantity influences the balance between solar energy capture and utilisation in photosynthesis, affecting concomitantly the downstream processes of central carbon and nitrogen metabolism as well as cellular growth and division. High light stress often results in metabolic flux imbalances, photo-oxidative stress and/or slower development of plants or inhibition of microalgal cell division (Foyer and Noctor, 2005; Li et al, 2009b; Miyagishima and Tanaka, 2021; Sanchez-Tarre and Kiparissides, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that for the maintenance of the highest photosynthetic performance in C. merolae cells exposed to long-term RL illumination, no metabolic energy investment is allocated to de novo synthesis of light harvesting components. In contrast to C. merolae , long-term application of varying light quantity and quality of Chlamydomonas reinhardtii cells has led to upregulation of the RuBisCo small subunit under red phototrophic growth, implying an increased demand for energy generation in this green microalga required to establish a shorter cell cycle and maintain a rapid duplication rate in conjunction with increased photosynthetic efficiency as well as reduced mutual shading across the light path (Sanchez-Tarre and Kiparissides, 2021). The same study showed that metabolic energy investment is based on transcriptomic upregulation of fatty acid biosynthesis and cell cycle components, which ensures shortening of the cell cycle and maintenance of a rapid duplication rate (Sanchez-Tarre and Kiparissides, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation